Collab4All: a method to foster inclusion in computer-supported collaborative work. - Luque, Leandro (2018)
During the last decades, the research field of Computer-Supported Collaborative Work has made impressive progress in proposing theories, techniques, and tools to support collaborative work in different settings. Nevertheless, despite the advances in the field and its branches, individuals with impairments still face inclusion challenges when performing computer-supported collaborative activities. In order to take part in such type of activities, individuals are expected to have skills and knowledge that may be affected by impairments. In the beginning of this PhD research, we studied means to include an individual with blindness in diagram-based activities conducted as part of software engineering lectures taught by the thesis author. As part of that, we noticed that researchers and practitioners generally did not follow any collaboration-oriented method to address accessibility issues when designing or redesigning collaboration supportive systems, also known as groupware. In this context, we decided to focus our attention on this gap. As a result, we developed Collab4All, a method to support the identification of potential challenges as well as alternative solutions that may arise when designing or redesigning accessible and inclusive groupware. As a proof of concept, we applied Collab4All to the aforementioned scenario of including individuals with blindness in diagram-related learning activities. Based on our findings, we documented some suggestions to researchers and developers working in this application scenario. The present document contains detailed information about this research process. We consider that the method proposed in this thesis, its application results and the groupware we developed, named Model2gether, are the field of computer-supported collaborative work involving people with impairments.